Potensi Penerapan Weekend Detention di Indonesia Sebagai Upaya Percepatan Resosialisasi Pelaku Tindak Pidana - Tigor Hamonangan Napitupulu (Unnes Law Journal, 2013)
This study aims to determine the existence of weekend detention in prison and possible implementation and formulation of weekend detention in pidana permasalahan law reforms that were examined in this study werein this study the authors used research methods normative juridical approach to legislation, concepts, philosophies, perbandingan. For analyzing the data, researchers used descriptive analysis or presentation with an overview of the subject and object of research as research that has been didapatkan. Result research shows that in practice in prison with no coaching model of weekend detention. But in Indonesia has a program of assimilation regulated in Law Number 12 Year 1995 concerning Correctional further stipulated by Government Regulation No. 28 Year 2006 on Amendment to Government Regulation No. 32 Year 1999 on Terms and Procedures for Implementation of the Rights of prisoners, which basically resemble weekend Detenion system, only assimilationapplied to all inmates eligible administrative and substantive weekend detention while expressly formulated to be applied to all inmates who were threatened with a period of time corresponding provisions of existing law.